Valorando las actividades de enfermería en el control prenatal desde la experiencia de la gestante - Guerra, Nayibe (2019)
Objective: To interpret the assessment of nursing activities in prenatal care from the pregnant woman's experience. Materials and Methods: The research is qualitative, hermeneutical phenomenological approach. As an information gathering technique that is used is the in-depth interview, through direct meetings with the 2 key actors with pseudonyms of water and sun. For the development of this study and data analysis was the Spiegelberg method that allows to study the field of consciousness and explore the people in study, based on their experiences. Results: From the analysis of the results, 2 categories are derived: Nursing actions sense of commitment and concern, most frequent risk factors. From these categories it can be deduced that prenatal care is of the utmost importance because it allows the identification of risks during childbirth and thus avoid complications during its development, where diseases during pregnancy stand out as causes of maternal mortality. Conclusions: The final considerations reflect the need for an approach that establishes a more open environment that allows encounters of familiarity, trust, respect for each other and go beyond the activities required by the institution. In addition, the essence that gives nursing to the importance of caring for the mother and child in prenatal control; this gives an opening towards the humanization of care in its broadest sense, since there are expressions of respect for life and the human condition.